Hardy spaces Hp and BMO: A brief clasicc overview - Ortiz Fernández, Alejandro (2022)
In this brief note we give an overview of Hardy spaces Hp and bounded mean oscillation spaces, BMO, two classic spaces that have played an important role in investigations of central branches in harmonic analysis. The given bibliography opens paths to follow in this field.